Oral Health Outcomes for Children in Hawaii: Not Much to Smile About - Deborah Mattheus; Maureen Shannon (Journal of Dental Problems and Solutions - Peertechz Publications, 2015)
Oral health has become a major topic of discussion in the State of Hawaii based on the unreasonably high rates of dental caries in children, which are almost twice the average rates for children living in the mainland. Lack of water fluoridation, absence of a state dental school and recent efforts to start rebuild the previously dismantled oral health branch at the Department of Health may be contributing to these poor oral health outcomes. However, there are many more known caries risk factors which may be socially, physiologically, culturally and economically driven that have yet to be documented within the State of Hawaii. While community assessments may evaluate oral health needs of the overall community, low income and vulnerable populations such as pregnant women and children deserve special attention and priority. Identification of risk factors amenable to change, such as families' oral health beliefs and behaviors should be clearly documented and considered in the process of developing future oral health initiatives as a means to improve oral health outcomes for children and families in Hawaii.